2000
DOI: 10.1038/sj.bmt.1702584
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile myelomonocytic leukemia relapsing after allogeneic bone marrow transplantation successfully treated with interferon-alpha

Abstract: Summary:We report a 5-year-old boy with juvenile myelomonocytic leukemia (JMML) which relapsed after an allogeneic bone marrow transplant who was successfully treated with interferon-␣ (IFN-␣). One year after starting the therapy, he remains clinically well and in complete remission while continuing treatment with IFN-␣ and bestatin. Although the precise mechanism by which remission was induced is uncertain, a GVL effect combined with a direct antileukemia effect of IFN-␣ may be responsible. Further assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Withdrawal of immunosuppressive drugs is usually the first measure, which by itself can control leukemia in a limited number of patients. Several reports [25][26][27][28][29][30] and the clinical course of patient CZ019 in this series indicate the efficacy of withdrawal of immunosuppressive therapy in some patients with relapsed JMML, suggesting a GVL effect in JMML. In the case of nonresponse and for patients suffering disease recurrence after discontinuation of immunosuppressive agents, DLI or second HSCT may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawal of immunosuppressive drugs is usually the first measure, which by itself can control leukemia in a limited number of patients. Several reports [25][26][27][28][29][30] and the clinical course of patient CZ019 in this series indicate the efficacy of withdrawal of immunosuppressive therapy in some patients with relapsed JMML, suggesting a GVL effect in JMML. In the case of nonresponse and for patients suffering disease recurrence after discontinuation of immunosuppressive agents, DLI or second HSCT may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that chronic graft‐ versus ‐host disease (GVHD) was associated with a lower risk of relapse and improved survival (Manabe et al , 2002; Smith et al , 2002). Withdrawal of immunosuppressive drugs can control leukaemia in some patients (Rassam et al , 1993; Lutz et al , 1996; MacMillan et al , 1998; Orchard et al , 1998; Kressler et al , 1999; Ohta et al , 2000). There have been a few reports on patients successfully treated by donor leucocyte infusion (DLI) (Matthes‐Martin et al , 2000; Worth et al , 2003; Neudorf et al , 2004; Pulsipher et al , 2004).…”
mentioning
confidence: 99%
“…The patient achieved 100% donor chimerism 2 months after starting IFN, maintaining the CR for 7 months on IFN and bestatin therapy at the time of the report. 6 Mackinnon et al demonstrated that escalating DLI doses could achieve complete leukemia response with less GVHD. 10 Following this approach, we gave cytoreductive chemotherapy followed by an initial DLI dose of 1 Â 10 6 CD3 þ cells/kg resulting in progressive disease and worsening donor T-cell chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…2 In spite of the well-documented efficacy of post transplant immunomodulation in other disorders, published work suggesting a graft-versus-leukemia (GVL) effect of post-transplant donor lymphocyte infusion (DLI) or intereferon in JMML is limited, and responding patients have all had monosomy-7 JMML. [4][5][6] We describe a patient who relapsed early after unrelated allogeneic bone marrow transplantation for non-monosomy-7 JMML in whom DLI induced a partial response, and the addition of interferon-alpha (IFN) likely contributed to attaining and sustaining a prolonged complete remission. This observation suggests a role for post-transplant immunotherapy approaches in non-monosomy-7 JMML.…”
mentioning
confidence: 99%